Research on Image Recognition Applications Driven by Artificial Intelligence - Xiang, Yuyun (Transactions on Computer Science and Intelligent Systems Research, 2024)
With the rapid development of artificial intelligence and machine learning technologies, image recognition technology has become a key force driving progress in many fields. Deep learning and machine learning algorithms have made remarkable progress in image recognition. Therefore, this article deeply explores the role of image recognition technology in three aspects: autonomous driving, medical imaging and face recognition. This article concludes that autonomous driving technology mainly relies on artificial intelligence and machine learning. It perceives the environment in real time through sensors and perception modules, and formulates driving strategies through decision-making and control modules to ensure the safe driving of vehicles. In medical image analysis, image recognition technology is used for feature extraction, image segmentation, and classification to assist doctors in disease diagnosis and treatment planning. In face recognition technology, through the three stages of face detection, face alignment and final recognition, individual identities are confirmed to improve the accuracy and efficiency of recognition. In conclusion, image recognition technology plays a vital role in the above fields, improving the intelligence and reliability of the system.